Literacy Culture and Digital Literacy in Elementary Schools - Moh Toharudin; Hana Kartika Sari; Budi Adjar Pranoto; Rila Melyana Fitri (IAIN Palopo, 2021)
The purpose of the study was to describe the implementation of literacy culture and digital literacy, as well as identify the supporting and inhibiting factors of literacy culture and digital literacy in increasing reading interest of elementary school students. This research uses a case study qualitative approach. Data collection techniques with participatory observation, interviews, and documentation. The validity of the data using triangulation techniques. This research was conducted at SD Negeri Kecipir 01 Brebes, Central Java. The results of this study are: 1) the implementation of literacy culture, namely: reading corner, reading 15 minutes before learning, library procurement; 2) Implementation of digital literacy by: E-library, a digital guide for teachers in learning; 3) Supporting factors: The role of schools by providing infrastructure suggestions, students' reading interest, the role of parents, teachers have a good learning spirit; 4) Inhibiting factors: incomplete infrastructure, student conditions and an unsupportive environment, lack of student interest in reading, and lack of parental supervision.